2011
DOI: 10.1007/s00405-011-1848-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Helicobacter pylori in nasal polyposis using polymerase chain reaction, urease test and culture

Abstract: The aim of this study was to identify the presence of Helicobacter pylori in nasal polyp specimens of patients with nasal polyposis. A cross-sectional study with control group was performed on fresh tissue samples from 25 patients with nasal polyps, and 25 persons with concha bollusa (control group). Patients with symptoms of gastroesophageal reflux (GERD) were not enrolled. Samples were studied by three methods: polymerase chain reaction (PCR), culture, and urease test. All the diagnostic tests were negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…It has to be freshly prepared before applying the test, making it time consuming. Szczygielski et al [36] and Nemati et al [33] could not prove any association between H. pylori and nasal polyps on the basis of urease test. Khademi et al [24] and Kaviani et al [19] reported false positivity in their study due to some other bacteria with urease activity.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has to be freshly prepared before applying the test, making it time consuming. Szczygielski et al [36] and Nemati et al [33] could not prove any association between H. pylori and nasal polyps on the basis of urease test. Khademi et al [24] and Kaviani et al [19] reported false positivity in their study due to some other bacteria with urease activity.…”
Section: Resultsmentioning
confidence: 94%
“…Burduk et al [21] believed that PCR assay is an appropriate method for detection of H. pylori in biopsy specimens, as culture is difficult to achieve. However, Nemati et al [33], Abbasi et al [34], and Ozyurt et al [20] could not yield a significant result employing PCR.…”
Section: Resultsmentioning
confidence: 96%
“…Nemati (29) , who found no intranasal H. pylori in any subjects, had excluded GORD sufferers from the study.…”
Section: Pathogenic Factorsmentioning
confidence: 99%
“…19,21 Nemati et al showed culture test negative in his studies, where as in our study 3 (8.57%) cases showed positive growth in culture media. 22 So IHC and culture test can be regarded as highly sensitive and specific which can detect the low concentration of bacteria and truly positive cases, so the true incidence of H. pylori in our study is 3 (8.57%). Culture is cheap and easily available method when compare to IHC which is costly and not easily available and particularly used in research purpose.…”
Section: Resultsmentioning
confidence: 71%